Maximum eigenvalue versus trace tests for the cointegrating rank of a VAR process - Helmut Lütkepohl; Pentti Saikkonen; Carsten Trenkler (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
The properties of a range of maximum eigenvalue and trace tests for the cointegrating rank of a vector autoregressive process are compared. The tests are alilikelihood ratio type tests and operate under different assumptions regarding the deterministic part of the data generation process. The asymptotic distributions under local alternatives are given and the local power is derived. It is found that the local power of corresponding maximum eigenvalue and trace tests is very similar. A Monte Carlo comparison shows, however, that there may be slight differences in small sampies. The trace tests tend to have more distorted sizes whereas their power is in some situations superior to that of the maximum eigenvalue tests.
urn:nbn:de:kobv:11-10048091
Keywords: 330